1986
DOI: 10.1143/jjap.25.1490
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Nitride Films Prepared by Plasma-Enhanced Chemical Vapour Deposition (PECVD) of SiH4/NH3/N2 Mixtures: Some Physical Properties

Abstract: Experimental data are presented on the effects of varying deposition parameters of SiH4/NH3 gas flow ratio, rf power, deposition pressure and substrate temperature, on the deposition rate, refractive index, hydrogen content and etch rates of PECVD silicon nitride films. BHF etch rate in these films are generally high and this is shown to be associated with the high hydrogen content. N-H and Si-H bond concentrations are measured in the range 1-4×1022 cm-3. The substrate temperature dependence of the etch rate e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The ratio of H bonded to N over that bonded to Si ([N--H]/[Si--H]) increases with NH3/SiH4 (18) and with x (19). Refractive index decreases with increasing NHJSiH4 (17,20) and with increasing [N--H]/[Si--H] (21), and the optical bandgap increases with x (22). Etch rate in aqueous HF increases with NHJSiH4 (20) and with [N--H]/[Si--H] (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio of H bonded to N over that bonded to Si ([N--H]/[Si--H]) increases with NH3/SiH4 (18) and with x (19). Refractive index decreases with increasing NHJSiH4 (17,20) and with increasing [N--H]/[Si--H] (21), and the optical bandgap increases with x (22). Etch rate in aqueous HF increases with NHJSiH4 (20) and with [N--H]/[Si--H] (21).…”
Section: Discussionmentioning
confidence: 99%
“…Refractive index decreases with increasing NHJSiH4 (17,20) and with increasing [N--H]/[Si--H] (21), and the optical bandgap increases with x (22). Etch rate in aqueous HF increases with NHJSiH4 (20) and with [N--H]/[Si--H] (21). The general trend is that increasing the NHjSiH4 ratio and the power lead to higher x and higher [N--H]/[Si--H], which results in lower refractive index and in higher bandgap and HF etch rate.…”
Section: Discussionmentioning
confidence: 99%
“…Szweda 9 showed that both conventional thermal annealing and flash-lamp annealing increase the refractive index and decrease the thickness of silicon nitride films. Ling et al 10 showed that increase in deposition temperature increases the density and refractive index and lowers the etch rate and hydrogen content of the film. However, no systematic study has been conducted to assess annealing-induced changes as a function of as-deposited refractive index and their impact on device performance.…”
Section: Introductionmentioning
confidence: 99%
“…In the PECVD process, the deposition pressure is one of the most important parameters affecting the deposition rate [50]. High pressures result in shorter mean free paths, lower electron temperatures, and reduced dissociative reactions that require high threshold energy.…”
Section: Gas Pressure Dependenciesmentioning
confidence: 99%